Comparison of the human bone matrix gelatin (HBMG) with autogenous bone graft in reconstruction of the parietal bone defects in rat: a histological and radiographic study - Hossein Shahoon; Hamid Reza Azimi; Camellia Kianbakht (Tabriz University of Medical Sciences, 2009)
Background and aims. Autogenous bone graft is commonly used for reconstruction of bone defects in routine surgical procedures. The complexity of producing bone grafts and their application has lead to the use of human bone matrix gelatin (HBMG). The present study was conducted to compare the efficacy of HBMG and autograft on the reconstruction of bone defects in rats.
Materials and methods. In this cross-sectional, experimental study, two defects were put on left and right sides of parietal bone of rats. HBMG was placed randomly on defects of one side and autograft in the defects of the other side. All specimens were assessed and compared with each other according to histological and radiographic characteristics. Other assessments included amount and the rate of bone formation, inflammation signs, fibrosis tissue and cartilage formation and also radiographic characteristics of grafts, assessed by digital and film-based methods. Mann-Whitney U test was used for statistical analysis.
Results. The results showed a reduction of inflammation and an increase in new bone formation in both groups in 7, 14, 28 and 60 days after surgery. Bone formation with HBMG on day 24 was more than autograft. However, there was no significant difference between the groups on day 60. Superiority of digital method to film-based method of imaging was also observed.
Conclusion. Although HBMG has the same efficacy as autograft, the rate of bone reconstruction with HBMG is higher. HBMG also induces focal, rather than peripheral, bone construction in the defect.